Oral health, dental treatment, and medication related osteonecrosis of the jaw in multiple myeloma - a longitudinal cohort study - Richard Olofsson; Magdalena Korytowska; Ulrica Almhöjd; Annica Almståhl; Hülya Cevik-Aras (BMC, 2024)
Abstract Objective The objective of the present study was to investigate oral health status, oral health related quality of life, and identify risk factors associated with invasive dental treatment and medication related osteonecrosis of the jaw in patients with multiple myeloma. Material and methods Patients newly diagnosed with multiple myeloma (n = 144) referred between January 2015 and September 2022 were retrospectively included. The patients underwent a thorough clinical and radiological oral examination and odontogenic infections were treated before the start of bisphosphonate treatment. The patients were followed annually, including clinical and radiological examinations. The oral health related quality of life was investigated by the OHIP-14 questionnaire. Results Dental treatment (RR = 7.75), receiving combination antineoplastic therapy≥3 (RR =4.13), periodontitis (RR = 4.21), and reduced number of teeth (RR = 2.87) were associated with an increased risk of medication related osteonecrosis of the jaw. The response rate of the OHIP-14 questionnaire was 70.2%. Oral pain or discomfort in the mouth related to the medical treatment was reported by 30.5%. Conclusion Dental screening and treatment planning in patients with Multiple Myeloma may result in fewer oral infections and fewer interruptions of the medical treatment of myeloma.